2012
DOI: 10.1007/s00216-011-5704-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced vibrational spectroscopy of B vitamins: what is the effect of SERS-active metals used?

Abstract: Surface-enhanced Raman scattering (SERS) spectroscopy and surface-enhanced infrared absorption (SEIRA) spectroscopy are analytical tools suitable for the detection of small amounts of various analytes adsorbed on metal surfaces. During recent years, these two spectroscopic methods have become increasingly important in the investigation of adsorption of biomolecules and pharmaceuticals on nanostructured metal surfaces. In this work, the adsorption of B-group vitamins pyridoxine, nicotinic acid, folic acid and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Even though the SERS spectra of FA have been investigated experimentally both on colloids and metallic surfaces, to the best of our knowledge, there are no previous reports of the adsorption studies and computed vibrational frequencies of FA in metallic surfaces nanostructured. The assignment of Raman bands of FA in a previously reported study was incomplete, and a deeper analysis of all vibrational modes of FA is warranted. In the following paragraph, the complete assignment of the Raman bands of FA is presented using both experimental and theoretical spectra (see summarized data in Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the SERS spectra of FA have been investigated experimentally both on colloids and metallic surfaces, to the best of our knowledge, there are no previous reports of the adsorption studies and computed vibrational frequencies of FA in metallic surfaces nanostructured. The assignment of Raman bands of FA in a previously reported study was incomplete, and a deeper analysis of all vibrational modes of FA is warranted. In the following paragraph, the complete assignment of the Raman bands of FA is presented using both experimental and theoretical spectra (see summarized data in Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The calculations were carried out using the GAUSSIAN 09 software package. [35] Results and discussion Raman spectra of FA Even though the SERS spectra of FA have been investigated experimentally both on colloids and metallic surfaces, [12,19,20] to the best Figure 2. Density functional theory calculated (blue) and experimental (red) surface enhanced Raman scattering (SERS) spectra of folic acid using silver-capped silicon nanopillar substrates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman measurements of vitamin B12, therefore, have the potential to yield both useful and innovative results. A strong case can be provided by other vitamins; SERS measurements of vitamin C show a detection behavior that closely matches the performance of HPLC measurements by using a structured silver substrate to enhance the Raman signal (129), and SERS has also been identified as a reliable technique to build up libraries of spectral signature for vitamin (130). Recent approaches such as producing SERS-active biotags for the characterization of biological samples have shown that the intensity of the SERS signal can be as high as that of fluorescencebut with the added advantage of unique identification of the compound (131) which represents an exciting step towards detecting physiologically-relevant concentration of vitamin B12.…”
Section: Raman Spectroscopymentioning
confidence: 81%